Evidence for trial-by-trial dynamic adjustment of task control in unmedicated adults with OCD. (March 2020) - Kalanthroff, Eyal; Marsh, Rachel; Hassin, Ran R.; Simpson, Helen Blair
Abstract: According to the conflict monitoring theory, executive control requires two separable processes: conflict-monitoring and conflict-resolution. Deficits in executive control have been observed in adults with obsessive-compulsive disorder (OCD). However, it is not yet clear whether these deficits can be attributed to deficits in conflict-monitoring, in conflict-resolution, or in both. We examined this question by administrating the Simon task to 67 unmedicated adults with OCD and 67 matched controls. The interference effect (incongruent minus congruent) was used to measure conflict-resolution. Trial-by-trial dynamic adaptation (i.e., the Gratton effect), which is indicated by smaller interference effect after conflict-laden trials compared to after non-conflict-laden trials, was used to measure conflict-monitoring. A similar interference effect was found in both the OCD and HC groups with no significant between group differences. Following incongruent trials, the interference effect became smaller for the control group as expected, but was completely eliminated for the OCD group. These data add to the accumulating evidence indicating that conflict-resolution is not globally deficient in unmedicated OCD patients and provide direct evidence that conflict-monitoring is heightened in OCD patients. Our results challenge the assumption of cognitive inflexibility in OCD and highlight the importance of studying unmedicated subjects when investigating executive control. Highlights: 67 unmedicated adults with OCD and 67 matched controls completed the Simon task. A similar interference effect was found in both groups. Trial-by-trial adaptation (the Gratton effect) was more robust in OCD patients. No evidence for deficit in conflict resolution in unmediated OCD patients. Unmedicated OCD patients exhibited heightened conflict monitoring.